2002
DOI: 10.1093/carcin/23.10.1695
|View full text |Cite
|
Sign up to set email alerts
|

Chfr expression is downregulated by CpG island hypermethylation in esophageal cancer

Abstract: Cell cycle progression is monitored by checkpoint mechanisms to ensure the integrity of the genome and the fidelity of sister chromatid separation. Failure of such checkpoint functions results in genomic instability, a condition that predisposes cells to neoplastic transformation and tumor progression. Recently, Scolnick and Halazonetis defined a new mitotic checkpoint that acts at prophase and delays chromosome condensation in response to mitotic stress, and identified a gene, named checkpoint with FHA and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
85
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 20 publications
5
85
1
1
Order By: Relevance
“…In contrast, cancer cell lines that lack CHFR enter metaphase without delay, with ectopic expression of CHFR necessary and sufficient to restore cell-cycle delay (Scolnick and Halazonetis, 2000). Recent studies of human tumours have shown that Chfr inactivation can be due to hypermethylation of CpGs in the promoter region (Mizuno et al, 2002;Shibata et al, 2002). However, whether Chfr promoter hypermethylation is involved in gastric cancer has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, cancer cell lines that lack CHFR enter metaphase without delay, with ectopic expression of CHFR necessary and sufficient to restore cell-cycle delay (Scolnick and Halazonetis, 2000). Recent studies of human tumours have shown that Chfr inactivation can be due to hypermethylation of CpGs in the promoter region (Mizuno et al, 2002;Shibata et al, 2002). However, whether Chfr promoter hypermethylation is involved in gastric cancer has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Northern blot analysis of Chfr using RNA from eight colon, osteosarcoma and neuroblastoma cancer cell lines revealed that Chfr expression was absent in three cell lines (Scolnick and Halazonetis, 2000). Loss of Chfr expression due to hypermethylation of a CpG island in the promoter region has been observed in tumour cell lines and primary cancers of the lung, oesophagus and colon (Mizuno et al, 2002;Shibata et al, 2002;Corn et al, 2003;Toyota et al, 2003). Thus, it is possible that Chfr promoter hypermethylation is also involved in gastric carcinogenesis.…”
mentioning
confidence: 99%
“…To evaluate the association between CHFR mRNA expression and CHFR immunohistochemical protein expression in NSCLC, we performed laser capture microdissection to collect cancer cells selectively in 20 lung cancer cases (adenocarcinoma, cases 1-10; squamous cell carcinoma, cases [11][12][13][14][15][16][17][18][19][20] as previously reported. 27 Before microdissection, frozen sections were cut into 8-lm-thick slices and stained with Giemsa, then dried with ethanol followed by xylene treatment as previously described, with minor modification.…”
Section: Evaluation Of Immunohistochemical Stainingmentioning
confidence: 99%
“…After mRNA extraction, reverse transcription and real-time quantitative RT-PCR were carried out in each case. The data were then compared to the immunohistochemical protein expression in matched formalin-fixed and paraffin-embedded tissue (cases [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Various levels of messenger RNA expression of the CHFR were detected in NSCLC (Fig.…”
Section: Correlation Between Mrna and Immunohistochemical Protein Expmentioning
confidence: 99%
See 1 more Smart Citation